Digital Media Preferences and Motivational Dynamics in EFL Learning: A Case Study of English Education Students at STKIP Paracendekia NW Sumbawa - Ikhsan, Al; Jazadi, Iwan; Tarihoran, Irfan Hamonangan (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2026)
The integration of digital and social media has profoundly reshaped how English as a Foreign Language (EFL) learners engage with language learning. This study investigates students’ preferred media platforms, the underlying motivational factors, and the challenges they face when using digital tools to enhance English proficiency. Employing a qualitative descriptive case study design, ten English Education students at STKIP Paracendekia NW Sumbawa were interviewed and observed, with the data analyzed thematically using Braun and Clarke’s (2006) framework. Findings reveal that YouTube, TikTok, and Instagram constitute the dominant learning ecosystem, offering multimodal exposure that promotes listening, pronunciation, and vocabulary development. Students’ media choices were influenced by accessibility, enjoyment, and autonomy, reflecting principles of Self-Determination Theory and learner autonomy. However, participants also faced obstacles, including distractions, unreliable content, and limited internet access. The study proposes a Dynamic Model of Media-Motivated Autonomy that illustrates how intrinsic motivation, self-regulation, and cognitive engagement interact to sustain language learning. These findings underscore the pedagogical importance of integrating students’ preferred media into EFL curricula while fostering digital literacy and critical awareness. Implications are offered for educators, curriculum designers, and policymakers to promote technology-enhanced, learner-centered English instruction.